Practical Hexo a hands-on introduction to building blogs using the Hexo framework - Libby, Alex (Apress, 2020)
Leverage the power of Hexo to quickly produce static blog sites that are efficient and fast. This project-oriented book simplifies the process of setting up Hexo and manipulating content, using little more than a text editor and free software. It will equip you with a starting toolset that you can use to develop future projects, incorporate into your existing workflow and allow you to take your websites to the next level. Hexo is based on JavaScript and Node.js, two of the biggest tools available for developers: you can enhance, extend, and configure Hexo as requirements dictate. With Hexo the art of possible is only limited by the extent of your imagination and the power of JavaScript and Node.js. Practical Hexo gets you quickly acquainted with creating and manipulating blogs using a static site generator approach. You will understand how to use the Hexo framework to rapidly create and deploy blogs that are performant, with the minimum of fuss, then extend and customize your content using plugins and themes. You will work through some practical projects to help solidify your skills, and put them into practice. You will: Implement the Hexo framework in a project Customize and extend content Consider maintenance requirements and how they compare to other blog systems Apply skills to practical, real-world projects Create themes and build plugins Make changes using other tools and libraries.